Studies regarding the Use of Pneumatic Muscles in Precise Positioning Systems - Petre, Ioana Mădălina (Applied Sciences MDPI, 2021)
The paper presents the methods and results of an experimental study that highlights the behavior of a pneumatic actuator under different pressures and with different loads applied. One important challenge that occurs in the application of pneumatic muscles is the phenomenon of hysteresis, which causes a nonlinear relationship between the input–output values. The aim of this study is to identify the occurrence of hysteresis in the operation of a small pneumatic muscle in different conditions. Thus, different loads are attached to the free end of a pneumatic muscle and different successive pressures are applied in order to examine the hysteresis of the contraction ratio when the muscle is inflated and then deflated. The obtained equations that describe the relationship between the input pressure and the axial contraction are significant for reaching a high-performance position control. In this regard, the article proposes a solution to increase positioning accuracy based on pressure control using a proportional pressure regulator and a programmable logic controller.
Keywords: pneumatic muscle; hysteresis; axial contraction; positioning systems